The Galician entrepreneurship internationalization matrix: A regulatory framework - Javier Bouzas Arufe; Marta Portela Maseda (Revista Galega de Economía)
This study examines the internationalization strategies of Galician entrepreneurs and SMEs, focusing on early internationalization trends. The main objective is to develop a regulatory framework that enables entrepreneurs and established SMEs to approach foreign markets effectively. From a qualitative approach, the research analyzed data from Galician firms to construct the Galician Entrepreneurship Internationalization (GEI) matrix. Data were collected through surveys and supplemented from the Vigo Free Trade Zone database, covering exporting companies founded between 1999 and 2021. Qualitative analysis and matrix modeling were applied to categorize firms into distinct internationalization stages, considering factors such as market breadth, export intensity, and speed of entry. Four company profiles emerged from the analysis. The findings reveal that newer companies, influenced by technological advances and favorable public policies, tend to internationalize within a year of inception. The GEI Matrix offers valuable insights for public policymakers and business managers aiming to promote early internationalization.